PENGARUH INDEPENDENSI, AKUNTABILITAS DAN KOMPETENSI TERHADAP KUALITAS AUDIT - Hari, Kurnia Krisna; Kusuma, Gumulyal Sonny Marce (Faculty of Economics and Business, 2024)
This research aims to see the influence of independence, accountability and competence on audit quality. Research analysis uses Structural Equation Mode with a Partial Least Square approach. Partial Least Square (PLS) is a variance-based structural equation analysis (SEM) that can test measurement models as well as test structural models. Researchers used primary data with a convenience sampling method in collecting data. The population in this study was 60 auditors who worked in KAP in the Palembang area. The sample in this study consisted of 46 respondents from auditors who worked at the Public Accounting Firm in the Palembang area. Research findings show that there is a partially significant positive influence between independence, accountability and competence on audit quality. The novelty of this research compared to other research lies in the analytical tools and approaches used.